Challenges of micro finance : an analysis of Nepal's urban micro finance industry - Timilsina, Saurav; Supasith Chonglerttham; Juthathip Jongwanich; Vatcharapol Sukhotu; Ministry of Foreign Affairs, Norway (Pathum Thani, Thailand : Asian Institute of Technology, 2013)
The mushrooming of urban microfinance institutions in Nepal has created many problems and few opportunities. The risesin the influx of urban immigrants who are poor and deprivedfrom mainstreamfinancial services have created a potentially huge market for urban MFIs. But the characteristics of urban poor are different from their rural counterparts and the replication of same rural model of micro-finance cannot serve urban poor and be financially viable at the same time.This paper has identified some of the major challenges of the urban micro-finance unique to Nepal, such as mission drift due to over commercialization, multiple lending and multiple borrowing leading to the over-indebtedness of clients beyond their capacity to repay and also lack of entrepreneur skills of clients needed to be successful in urban areas. Furthermore, formation ofcoherent and successful groups is very difficult in urban microfinance as it is plagued by high dropout rates, high default rates and lack of trust among group members.Central MIS system where all the information about clients can be gathered at real timewill help preventclient duplication, over indebtedness and default.Also allowing the withdrawal of funds from mandatory saving fund will discourage high dropout rates among the client.And finally, providing customized products will prevent dissatisfaction among clients.
A research study submitted in partial fulfillment of the requirementsfor the degree of Masters of Business Administration in Business Administration - MBA
Research report (M.B.A.) - Asian Institute of Technology, 2013
Keywords: Microfinance -- Nepal